Olive water use and crop coefficients from energy balance and radiometric canopy temperatures - Santos, Francisco L. (2016)
Biophysical and meteorological variables as well as radiometric canopy temperatures were collected in an intensive orchard near Évora, Portugal, with 28% ground cover by canopy and combined in a simplified two-source energy balance model (STSEB) to independently calculate the olive tree transpiration (T_STSEB) component of the total evapotranspiration (ETc). Sap flow observations were simultaneously taken in the same orchard allowing also for independent calculations of tree transpiration (T_SF). Model water use results were compared with water use estimates from the sap flow measurements. Good agreement was observed (R2=0.86, RMSE=0.20 mm d-1), with an estimation average absolute error (AAE) of 0.17 mm d-1. From June to August, on average olive water use were 1.92 and 1.89 mm d-1 for sap flow and STSEB model respectively, and 1.38 and 1.58 mm d-1 for the month of September. Results were also used to assess the olive basal crop coefficients (Kcb). Kcb estimates of 0.33 were obtained for sap flow and STSEB model, respectively, for June to August, and of 0.44 and 0.53 for the month of September. Basal crop coefficients were lower than the suggested FAO56 average Kcb values of 0.65 for June to August, the crop mid-season growth stage, and of 0.65 for the month of September, the end-season.